2016
DOI: 10.1021/acsami.6b07985
|View full text |Cite
|
Sign up to set email alerts
|

UV-Induced Oxygen Removal for Photostable, High-Efficiency PTB7-Th:PC71BM Photovoltaic Cells

Abstract: Solution-processed ZnO sol-gel or nanoparticles are widely used as the electron transporting layer (ETL) in optoelectronic devices. However, chemisorbed oxygen on the ZnO layer surface has been shown to be detrimental for the device performance as well as stability. Herein, we demonstrate that a chemisorbed oxygen removal based on a UV illumination of the ZnO surface layer under a nitrogen atmosphere can, simultaneously, improve power conversion efficiency and photostability of PTB7-Th: PC 71 BM based inverted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…It is observed that the devices using ZnO interlayers yielded an inflection around the Voc point when they were not subjected to UV activation. This suggests that the UV activation is necessary for the induction of photoconductivity and oxygen desorption in the un-doped ZnO layer and the elimination of the electron extraction barrier as also reported by other groups and may explain the lower photovoltaic performance of our reference devices with ZnO (which were not UV activated) as compared to other works [25,55,56]. On the contrary, there was negligible change in the performance of devices using HZO interlayer under illumination without the UV component.…”
Section: Resultssupporting
confidence: 75%
“…It is observed that the devices using ZnO interlayers yielded an inflection around the Voc point when they were not subjected to UV activation. This suggests that the UV activation is necessary for the induction of photoconductivity and oxygen desorption in the un-doped ZnO layer and the elimination of the electron extraction barrier as also reported by other groups and may explain the lower photovoltaic performance of our reference devices with ZnO (which were not UV activated) as compared to other works [25,55,56]. On the contrary, there was negligible change in the performance of devices using HZO interlayer under illumination without the UV component.…”
Section: Resultssupporting
confidence: 75%
“…Wide bandgap n‐type semiconductors such as ZnO, TiO 2 , and CdS have been extensively employed in photovoltaic devices as they readily crystalize with good semiconducting properties from a wet‐chemical fabrication process. CdS is a typical n‐type semiconductor with higher photostability compared to ZnO and TiO 2 and the CdS films have been prepared by various methods such as Chemical Bath Deposition (CBD), sputtering, and evaporation . CdS films have been extensively studied in Cu(In,Ga)Se 2 , Cu 2 ZnSn(S,Se) 4 , and CdTe solar cells as the electron transport layer.…”
Section: Introductionmentioning
confidence: 99%
“…PC 71 BM [34][35][36] ), we demonstrate that we can achieve a power conversion efficiency (PCE) of 11.1%, corresponding to the highest power conversion efficiency ever measured for that polymer. The applicability of this new optical cavity is quite general and may be used, in 3 principle, to enhance the performance of any other thin film photovoltaic technology.…”
Section: Introductionmentioning
confidence: 70%